Acrania-exencephalie in a live newborn delivered at term: A case report - Jeannot Baanitse Munihire; Bruce Ntamenya Simpezwe; Joshua Muhumuza; Sonye Kiyaka; Gabriel Shamavu Kakuru; Gisele Baabo Buholo (Elsevier, 2023)
Exencephaly is a rare fetal anomaly that is incompatible with extra uterine life. This malformation is characterized by partial or complete absence of the calvaria (cranium) called acrania with abnormal development of brain tissue.We present a case of a live acrania-exencephalic newborn to a 19 year old of parity 1 plus 1 in a non-consanguineous marriage delivered at 39 weeks of amenorrhea. Early prenatal ultrasound scan (USS), showed a single fetu sat 9 weeks with no deformity however at birth, acrania-exencephaly was diagnosed.The newborn died on the 3rd day of life and autopsy revealed exencephaly with deformed brain under a thick membrane without any other malformation.We present a rare fetal anomaly of acrania-exencephaly which persisted till term and was not detected by the prenatal ultrasound scan.